2010
DOI: 10.1111/j.1751-553x.2009.01168.x
|View full text |Cite
|
Sign up to set email alerts
|

BAALC and ERG expression in acute myeloid leukemia with normal karyotype: impact on prognosis

Abstract: Cytogenetic aberrations are important prognostic factors in acute myeloid leukemia (AML). About 45% of de novo AML lack cytogenetic abnormalities, so identification of predictive molecular markers might improve therapy. We studied the prognostic impact of brain and acute leukemia, cytoplasmic (BAALC) and ETS-related gene (ERG) expression in AML with normal karyotype. Pretreatment bone marrow samples from 30 cytogenetically normal AML patients were analysed for BAALC and ERG expression using real time RT-PCR. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 19 publications
6
24
1
2
Order By: Relevance
“…This finding is not in accordance with that reported by Eid et al [25], they stated that high expression of BAALC and ERG were found in 70 and 33.3 % of patients respectively. In addition Eid et al [25] stated that the high BAALC and ERG expression was correlated to both percentage of blast cells in the blood and BM, but did not associated with other clinical parameters of patients and high ERG expression was associated with higher white cell counts.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…This finding is not in accordance with that reported by Eid et al [25], they stated that high expression of BAALC and ERG were found in 70 and 33.3 % of patients respectively. In addition Eid et al [25] stated that the high BAALC and ERG expression was correlated to both percentage of blast cells in the blood and BM, but did not associated with other clinical parameters of patients and high ERG expression was associated with higher white cell counts.…”
Section: Discussioncontrasting
confidence: 96%
“…Also, high BAALC and ERG expression had inferior EFS, and OS. These findings are in parallel with that reported by Eid et al [25]. Univariate analysis revealed that High ERG and BAALC expression; showed a significant association with inferior EFS as well as shorter OS.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…ERG gene rearrangements have been identified in Ewing sarcoma and prostate cancer (8,9). Previous studies suggest that ERG overexpression is associated with inferior clinical outcome (10,11) and is an independent prognostic factor in cytogenetically normal acute myeloid leukemia (AML) (12)(13)(14). Furthermore, in acute T cell-lymphoblastic leukemia (T-ALL) patients, a high level of ERG expression has been associated with poor relapse-free survival (RFS) (15,16).…”
Section: Introductionmentioning
confidence: 99%